Suppression of Eosinophil Integrins Prevents Remodeling of Airway Smooth Muscle in Asthma - Januskevicius, Andrius; Gosens, Reinoud; Sakalauskas, Raimundas; Vaitkiene, Simona; Janulaityte, Ieva; Halayko, Andrew J.; Hoppenot, Deimante; Malakauskas, Kestutis (Frontiers in Physiology, 2017)
Abstract Background: Airway smooth muscle (ASM) remodeling is an important component of the structural changes to airways seen in asthma. Eosinophils are the prominent inflammatory cells in asthma, and there is some evidence that they contribute to ASM remodeling via released mediators and direct contact through integrin–ligand interactions. Eosinophils express several types of outer membrane integrin, which are responsible for cell–cell and cell–extracellular matrix interactions. In our previous study we demonstrated that asthmatic eosinophils show increased adhesion to ASM cells and it may be important factor contributing to ASM remodeling in asthma. According to these findings, in the present study we investigated the effects of suppression of eosinophil integrin on eosinophil-induced ASM remodeling in asthma. Material and methods: Individual combined cell cultures of immortalized human ASM cells and eosinophils from peripheral blood of 22 asthmatic patients and 17 healthy controls were prepared. Eosinophil adhesion was evaluated using eosinophil peroxidase activity assay. Genes expression levels in ASM cells and eosinophils were measured using quantitative real-time PCR. ASM cell proliferation was measured using alamarBlue® solution. Eosinophil integrins were blocked by incubating with Arg-Gly-Asp-Ser peptide. Results: Eosinophils from the asthma group showed increased outer membrane α4β1 and αMβ2 integrin expression, increased adhesion to ASM cells, and overexpression of TGF-β1 compared with eosinophils from the healthy control group. Blockade of eosinophil RGD-binding integrins by Arg-Gly-Asp-Ser peptide significantly reduced adhesion of eosinophils to ASM cells in both groups. Integrin-blocking decreased the effects of eosinophils on TGF-β1, WNT-5a, and extracellular matrix protein gene expression in ASM cells and ASM cell proliferation in both groups. These effects were more pronounced in the asthma group compared with the control group. Conclusion: Suppression of eosinophil-ASM interaction via RGD-binding integrins attenuates eosinophil-induced ASM remodeling in asthma. Trial registration: ClinicalTrials.gov Identifier: NCT02648074